Prácticas deportivas alternativas, Goalball como propuesta pedagógica para clases de educación física y su aplicación en las ciencias de la salud. (2022)
Although physical education is an area of study of formal content in schools, it has been transformed leaving behind traditional schemes and encompasses assessments based on standards and benchmarks, to give way to a new curricular approach that emphasizes teaching for socialization, to develop emotional intelligence, maintaining student motivation in school activities and transversalized knowledge to enhance the welfare and quality of life of the future adult. This documentary review article aims to present goalball as a pedagogical proposal for the physical education class framed in alternative sports practices, for this through the socio-critical paradigm, with a qualitative, descriptive and transversal approach. As main finding it was found that goalball not only keeps the players involved physically active, but also helps to develop skills that can be used in daily life, helps with awareness of their environment, mobility and orientation, as well as communication skills. Due to its inclusive design goalball projects as an excellent addition to any physical education curriculum, as in addition to being a popular Paralympic sport it has the potential to inspire all students to participate and grow not only as players, but as individuals celebrating inclusion, diversity and equal opportunities for all.